Автоматизована обробка персоналізованої медичної інформації для систем підтримки прийняття рішень - Мельникова, Наталія Іванівна (Національний університет "Львівська політехніка", 2014)
У дисертаційній роботі розв’язано актуальну наукову задачу підвищення якості обробки персоналізованої медичної інформації шляхом розроблення та вдосконалення методів і засобів аналізу даних для систем підтримки прийняття лікарських рішень. Проведений аналіз програмних та алгоритмічних засобів підтримки прийняття рішень у медичній галузі та введена класифікація медичних інформаційних систем за видами надання медичної допомоги. Розроблено метод прийняття рішень щодо визначення стандартної схеми для забезпечення лікувального процесу, шляхом обробки даних пацієнта з використанням теорії скінченних автоматів, що дає змогу моделювати стан хворого і уточнювати схему на кожному етапі лікувального процесу. Формалізовано модель СПЛР на основі концепції теорії автомата Мілі. Удосконалено метод прийняття рішень щодо персоналізації стандартних схем, шляхом пошуку введення оціночної функції появи наступного стану за наявності часово-залежних та часово-незалежних даних системи, що надає направленості при виборі необхідних цільових схем лікування. Визначено кількісну оцінку якості результатів застосування персоналізованих схем, шляхом формалізації якісних показників впливу на комплексний критерій стану пацієнта, що дає змогу корегувати або змінювати тактику лікування. Розроблено систему підтримки лікарських рішень, що моделює поведінку експерта при виборі персоналізованої терапевтичної схеми, що дозволило підвищити якість надання медичної допомоги хворим з різною патологією. В диссертационной работе решена актуальная научная задача повышения качества обработки персонализированной медицинской информации путем разработки и совершенствования методов и средств анализа данных для систем поддержки принятия врачебных решений. Проведенный анализ программных и алгоритмических средств поддержки принятия решений в медицинской отрасли и усовершенствована классификация медицинских систем по видам оказания медицинской помощи. Разработан метод поддержки принятия решений по определению стандартной схемы для обеспечения лечебного процесса, путем обработки данных пациента с использованием теории конечных автоматов, что позволяет моделировать состояние больного и уточнять схему на каждом этапе лечебного процесса. Формализована модель СПЛР на основе концепции теории автомата Мили. Определено количественную оценку качества результатов применения персонализированных схем, путем формализации количественных показателей влияния на качественный критерий состояния пациента, что позволяет корректировать или изменять тактику лечения. Разработана система поддержки врачебных решений, что моделирует поведение эксперта при выборе персонализированной терапевтической схемы, что позволило повысить качество оказания медицинской помощи больным с различной патологией. The dissertation contains research solved to date scientific task of improving the quality of treatment personalized health information through the development of information technology for making medical decisions and improve the quality of health care by formalizing criteria for comprehensive evaluation. The analysis software and algorithmic tools to support decision-making in the medical field and entered the medical classification systems by providing medical care, which enables to provide an assessment of the current state of development, use and implementation of existing health information technology and intellectual highlight previously unsolved problem. A decision support method for determining the standard scheme for the treatment process by handling patient data using the theory of finite state machines, which allows simulating the patient’s condition and refining the scheme at each stage of the treatment process. The doctor decision system support formalized model based on the concept of Mealy automat theory that proves the existence of functions of output signals, depending on the set of system states and input signals, that is the parameters of the patient. There are approved that the assignment of treatment is a special type of machine abstraction, using the description of the way of changing the state of a patient based on the achieved status and information received from the outside. The method of decision support regarding persona-lization from standard schemes chase by searching for the maximum occurrence hypothesis evaluation function in the presence of time-dependent data system is designed that provides orientation when selecting appropriate targeted treatment regimens. A method for evaluating the quality of the personalized schemes results by formalizing quantitative criteria and determine their impact on the qualitative indicators of the patient. This method allows correcting or changing the treatment strategy. The quantitative evaluation of the quality of the results of personalized schemes by formalizing quantitative criteria influence the quality indicators of the patient, allowing correct or modify treatment strategy. A system to support medical decisions that simulates the behavior of an expert in selecting of personalized therapeutic schemes is presented, thus improving the quality of medical care for patients with different pathologies. The architecture of doctor decision system support and related software are designed. They both allow us to assign custom scheme of conservative treatment. A quantitative evaluation of the results quality are at 13% higher than the results obtained using of schemes proposed information system WHONET5.
Автоматизированная обработка персонализированной медицинской информации для систем поддержки принятия решений
The automated processing of personalized health information for decision making support systems
Keywords: система підтримки лікарських рішень; скінченний автомат; персоналізована схема лікування; оцінка якості результатів; система поддержки врачебных решений; конечный автомат; персонализированная схема лечения; оценка качества результатов; the medical decision support system; finite state machines; personalized regimen; quality assessment results